Strategi Pembelajaran Sejarah Historical Problem Based Learning Melalui Media Katalog Sejarah (Katarah) Peninggalan Candi Kerajaan Hindu Budha di Malang Raya - Susmianto, Febry Adi; Wahyudi, Deny Yudho; Agung , Dewa Agung Gede (Cetta: Jurnal Ilmu Pendidikan, 2025)
History learning in schools still faces various challenges, particularly in terms of instructional innovation. The limited use of digital media and student-centered learning strategies has resulted in low student engagement and weak historical awareness. One subject that requires an innovative approach is the study of Hindu-Buddhist temple remains in the Malang Raya region, which holds significant educational and cultural value. This study aims to design a conceptual model of history learning based on Historical Problem-Based Learning (HPBL) integrated with a digital media tool called Katalog Sejarah (Katarah), in order to enhance learning effectiveness and contextual relevance. The research employs a Research and Development (R&D) approach using the ADDIE model, which consists of five phases: Analyze, Design, Develop, Implement, and Evaluate. This conceptual study focuses on the design phase without classroom implementation. The design results indicate that integrating HPBL with Katarah has the potential to create more participatory learning, foster critical thinking, and strengthen students’ historical literacy. Katarah, as an interactive visual medium, enables students to explore historical heritage digitally and independently. This model is also aligned with the principles of the Merdeka Curriculum, which emphasizes project-based learning and differentiation. The study concludes that the HPBL-Katarah conceptual model offers an innovative and contextual alternative for history learning and supports the achievement of the Profil Pelajar Pancasila, particularly in the dimensions of critical reasoning and global diversity. Further classroom implementation is needed to empirically test its effectiveness.